Automated Implementation Process of Machine Translation System for Related Languages - Vičič, Jernej; Homola, Petr; Kuboň, Vladislav (Computing and Informatics, 2016)
The paper presents an attempt to automate all data creation processes of a rule-based shallow-transfer machine translation system. The presented methods were tested on four fully functional translation systems covering language pairs: Slovenian paired with Serbian, Czech, English and Estonian language. An extensive range of evaluation tests was performed to assess the applicability of the methods.